Enhancing Teachers’ Competence in Developing ASYIIK Practicum Guidebooks (Innovative Science Activities in Chemistry Education) at MGMP IPA Semarang, Indonesia - Wardani, Sri; Sarwi, Sarwi; Susilaningsih, Endang; Susatyo, Eko Budi; Tuyarni, Tuyarni; Febriani, Wulan; Riyandino, Adyatma; Ulfa, Saidatul; Suwardi, Erman (Journal of Community Empowerment, 2025)
This community service program aims to enhance the competence of science teachers under MGMP IPA Semarang in developing the ASYIIK practicum guidebook (Innovative Science Activities in Chemistry Education). This initiative was based on the limited use of innovative and curriculum-based practicum guides, as well as the challenges many teachers face in designing engaging and applicable practicum activities. The training involved 60 teachers from 9 schools and was conducted through forum group discussions (FGD), guidebook reviews, and structured monitoring and evaluation. Activities included material presentation, mini-practicum sessions, and assignments related to guidebook development. The results showed that over 78% of participants successfully created practicum guidebooks that met the established criteria, indicating a significant improvement in their competence. The program produced several outcomes, including a publication in a nationally accredited SINTA 4 journal, electronic media coverage, a video highlight, and copyright registration. These findings suggest that the ASYIIK approach fosters contextual learning, integrates 21st-century skills, and improves students’ motivation and understanding in chemistry learning. In conclusion, the program reinforces the role of teachers as innovative and relevant designers of meaningful learning experiences.